Trends in Online Shopping Behavior Among the Millennial Generation - Maria Yuliastuti; Theresia Intan Putri Hartiana (Universitas Tribhuwana Tungga Dewi, 2026)
This research aims to describe the online shopping behavior of the millennial generation. Examining millennials is particularly compelling because the surge in e-commerce activity is closely tied to Generation Z and Millennial consumers, who collectively contribute 85% of total transactions. Moreover, the millennial generation bridges